2007
DOI: 10.1002/jmv.20974
|View full text |Cite
|
Sign up to set email alerts
|

Mutations associated with lamivudine‐resistance in therapy‐naïve hepatitis B virus (HBV) infected patients with and without HIV co‐infection: Implications for antiretroviral therapy in HBV and HIV co‐infected South African patients

Abstract: This was an exploratory study to investigate lamivudine-resistant hepatitis B virus (HBV) strains in selected lamivudine-naïve HBV carriers with and without human immunodeficiency virus (HIV) co-infection in South African patients. Thirty-five lamivudine-naïve HBV infected patients with or without HIV co-infection were studied: 15 chronic HBV mono-infected patients and 20 HBV-HIV co-infected patients. The latter group was further sub-divided into 13 occult HBV (HBsAg-negative) and 7 overt HBV (HBsAg- positive)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 28 publications
(33 reference statements)
2
53
3
Order By: Relevance
“…Even though such findings are rare, a similar report is also available from South Africa where ~30% of the naive occult HBV/HIV co-infected patients harbored 3TC resistance [63]. Previously, we observed high prevalence of 3TC resistance among the HIV/HBV co-infected subjects of eastern India who are on prolonged ART [64].…”
Section: Discussionmentioning
confidence: 70%
“…Even though such findings are rare, a similar report is also available from South Africa where ~30% of the naive occult HBV/HIV co-infected patients harbored 3TC resistance [63]. Previously, we observed high prevalence of 3TC resistance among the HIV/HBV co-infected subjects of eastern India who are on prolonged ART [64].…”
Section: Discussionmentioning
confidence: 70%
“…Other studies have reported primary 3TC resistance due to rt181T/S substitutions [10]. HBV mutations also occur in the absence of 3TC therapy and are thought to occur naturally in HBV carriers who have not been treated with the drug, implying that pre-existing mutations may be transmitted or contribute toward early emergence of 3TC resistance during therapy [11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…Of note, none of the 12 testing positive for HBV DNA was anti-HCV positive, a feature said to be associated with occult HBV in other settings [Cacciola et al, 1999]. On the other hand, with the availability of highly active antiretroviral treatment (HAART) in Africa in the recent years, the prevalence of lamivudine resistant mutants is increasing [Selabe et al, 2007]. Lamivudine resistant mutations have been reported to cause the amino acid substitutions in both the pol and envelope genes, thus affecting HBsAg and its detection [Ono-Nita et al, 1999;Yeh et al, 2000].…”
Section: Discussionmentioning
confidence: 97%